SUCELL Test Conditions Optimization of HELOS/BF Laser Particle Size Analyzer - LU Xin-cheng; CAO Jing-yang (Yankuang ceshi, 2013)
The Laser Particle Size Analyzer is being more widely used due to its fast test speed, convenient operation and good repeatability, to name a few of its qualities. However technical parameters of instrument and test conditions affect the results significantly. The test conditions of the HELOS/BF Laser Particle Size Analyzer were optimized by experiments described in this paper. The results indicate that samples with light specific-gravity or small particle size require lower stirring speed, higher ultrasonic intensity and longer ultrasonic time. Samples with heavy specific-gravity or large particle size require higher stirring speed, lower ultrasonic intensity and shorter ultrasonic time. The dispersant can accelerate the dispersion of the sample particles, especially for the small particle size samples. The low injection concentration (shading rate) with less particles leads to higher measured results for particle size because the weak signal causes bad representation for the samples. The high injection concentration leads to lower measured results based on the broad range of particle size distribution by multiple scattering. It suggests that the injection sample concentration (shading rate) between 10%-25% was appropriate for the HELOS/BF Laser Particle Size Analyzer.